2020
DOI: 10.1051/0004-6361/201937214
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric activity in bright contact binary stars

Abstract: Context. Studying chromospheric activity of contact binaries is an important way of revealing the magnetic activity processes of these systems. An efficient but somewhat neglected method for that is to follow the changes of the Hα line profiles via optical spectroscopy. Aims. Our goal was to perform a comprehensive preliminary analysis based on the optical spectral signs of chromospheric activity on the largest sample of contact binaries to date. Methods. We collected optical echelle spectra on 12 bright conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Chromospheric activity is another stellar activity occurring in LMCBs, which is revealed by excess emissions of certain specific spectral lines (e.g., Mg II λ280 nm, Ca II H and K (λ396.8 and 393.4 nm), Hβ (λ486.1 nm), Na I λ589.7 nm, Hα (λ656.3 nm), Ca II IRT (λ849.8, 854.2, and 866.2 nm), etc.) ranging from the ultraviolet to infrared regions (Barden 1985;Ruciński 1985;Kandulapati et al 2015;Mitnyan et al 2018Mitnyan et al , 2020Cheng et al 2019;Liu et al 2019). Previously, Barden (1985) noted that Hα excess emission is detected only for the more-massive component of a W-subtype system; this finding was recently confirmed for the VW Cep system by Mitnyan et al (2018), who also found a correlation between spottedness and the chromospheric activity of the system.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Chromospheric activity is another stellar activity occurring in LMCBs, which is revealed by excess emissions of certain specific spectral lines (e.g., Mg II λ280 nm, Ca II H and K (λ396.8 and 393.4 nm), Hβ (λ486.1 nm), Na I λ589.7 nm, Hα (λ656.3 nm), Ca II IRT (λ849.8, 854.2, and 866.2 nm), etc.) ranging from the ultraviolet to infrared regions (Barden 1985;Ruciński 1985;Kandulapati et al 2015;Mitnyan et al 2018Mitnyan et al , 2020Cheng et al 2019;Liu et al 2019). Previously, Barden (1985) noted that Hα excess emission is detected only for the more-massive component of a W-subtype system; this finding was recently confirmed for the VW Cep system by Mitnyan et al (2018), who also found a correlation between spottedness and the chromospheric activity of the system.…”
Section: Introductionmentioning
confidence: 86%
“…In addition, to investigate whether chromospheric activity occurs in the V505 Lac system, a spectral subtraction technique (Barden 1985;Montes et al 2000;Mitnyan et al 2018Mitnyan et al , 2020Şenavcı et al 2018) was applied to the Ca II H and K and Hα absorption lines; these lines are known to be optical diagnostic indicators of chromospheric activity. Before performing this task, we tested the consistency of the spectral synthesis described above by modeling two spectral regions: the Fe I λ495.7 nm region, which was used for temperature determination, and the λ558.0-564.0 nm region, which includes mostly photospheric lines (Şenavcı et al 2018).…”
Section: Spectrum Synthesismentioning
confidence: 99%
“…The similar depth minima in the light curve suggest that each star has a similar temperature. In a contact binary, each star typically has a similar effective temperature and in turn likely has a similar spectrum (e.g., Pribulla et al 2003;Mitnyan et al 2020). Assuming a contact binary configuration, we model the system as a contact binary in PHOEBE to constrain system parameters.…”
Section: Joint Radial Velocity and Photometry Modelingmentioning
confidence: 99%